Penyuluhan Infeksi Menular Seksual pada Mahasiswa Fakultas Pertanian Universitas Methodist Indonesia - Siagian, Laura Oktavian; Sihombing, Yan Pieter; Silangit, Thomas; Sinatra, Jadeny; Khu, Adrian; Safira, Eigia; Saragih, Damayanti; Reza, Yopi; Sinaga, Christina Leony; Banu, Rema Ibrena Enjelia; Marila, Dani; Yoganta, Alfri; Br. Ginting, Vini Vici; Zebua, Barukh Saro Talemta; Sarah, Putri (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
Sexually Transmitted Infections (STIs) are infections that are transmitted through sexual contact as well as outside of sexual contact. Transmitted through sexual contact can be vaginal, anal or oral; and sexual contact can come through contaminated objects, such as needles. Because Indonesia is the fifth country with the risk of sexually transmitted infections. So, this community service is carried out to reduce the incidence of sexually transmitted infections as well as prevent casual sex and increase students' insight. Most of these incidents are experienced by teenagers to young adults, namely around the age of 15-24 years. Students carrying out community service at the Indonesian Methodist Faculty of Agriculture were very enthusiastic when listening and had high curiosity about the information provided regarding Sexually Transmitted Infections.